Principles of cell and molecular biology - Lewis J Keinsmith (HarperCollins College, 1995)
This book presents a balanced treatment of both classical cell biology and modern molecular biology from an experimental approach. Its also provides. It provides both an explanation of the evolution of models and ideas and the most accurate data available for each concept. By introducing the fundamental principles that guide cellular organization and function, the book provides the crucial scientific evidence that led to the formulation of these central concepts.